Youth Screen Time and Behavioral Health Problems: The Role of Sleep Duration and Disturbances. Issue 4 (May 2016) - Parent, Justin; Sanders, Wesley; Forehand, Rex
ABSTRACT: Objective: The purpose of this study was to examine the indirect effect of youth screen time (e.g., television, computers, smartphones, video games, and tablets) on behavioral health problems (i.e., internalizing, externalizing, and peer problems) through sleep duration and disturbances. Methods: The authors assessed a community sample of parents with a child in one of the following three developmental stages: young childhood (3–7 yrs; N = 209), middle childhood (8–12 yrs; N = 202), and adolescence (13–17 yrs; N = 210). Path analysis was used to test the hypothesized indirect effect model. Results: Findings indicated that, regardless of the developmental stage of the youth, higher levels of youth screen time were associated with more sleep disturbances, which, in turn, were linked to higher levels of youth behavioral health problems. Conclusion: Children who have increased screen time are more likely to have poor sleep quality and problem behaviors.